Hedonism in the Young Generation: The Challenge of Pancasila Moral Education - Annisa Prajabti; Xo Ho Dac Kien; Muhammad Rasyid Ridho (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2022)
Globalization can be interpreted as a global process and everything becomes more modern, easy, sophisticated, and faster without the limitations of distance, space and time. Globalization is supported by a variety of technological innovations that help human life a lot. Inevitably, globalization creates various phenomena in various aspects of life. One example is the lifestyle of hedonism among the younger generation. Hedonism itself is a view of life that is manifested in the form of a lifestyle that makes worldly pleasure the purpose of life. Many people mistakenly apply this lifestyle of hedonism, perhaps unknowingly this has become a social disease. This hedonism attacks many millennials, where millennials are the next generation of young people who should be far from the nature of hedonism. The lifestyle of hedonism itself is difficult to avoid, there needs to be an awareness of each person. Indonesia has a very strong ancestral heritage to help young people free from the hedonism lifestyle that has become a disease, namely the five principles of Pancasila. The young generation needs to inculcate the strong personality contained in Pancasila and always implement it in daily life. The values ​​and meanings of Pancasila are the guiding principles of the nation, the personality of the nation, and the ideology of the nation that is most in line with the noble soul and personality of the Indonesian Nation.